2018
DOI: 10.1111/bcp.13706
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring‐guided definition of adherence profiles in resistant hypertension and identification of predictors of poor adherence

Abstract: This evidence highlights the high prevalence of poor adherence in patients with resistant hypertension and the need for caution in using invasive approaches. These preliminary data require validation in a larger cohort, to confirm the need for TDM in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
(42 reference statements)
1
30
0
1
Order By: Relevance
“…Generally, it refers to medication or drug adherence (Jimmy & Jose, 2011). Poor adherence to medication is common in individuals with hypertension (Avataneo et al, 2018) particularly among the elderly in Lo, Chau, Woo, Thompson, and Choi (2016). Adherence was related to better health outcomes such as quality of life (Park, Song, Shin, Jeong, & Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it refers to medication or drug adherence (Jimmy & Jose, 2011). Poor adherence to medication is common in individuals with hypertension (Avataneo et al, 2018) particularly among the elderly in Lo, Chau, Woo, Thompson, and Choi (2016). Adherence was related to better health outcomes such as quality of life (Park, Song, Shin, Jeong, & Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This, together with undisclosed suboptimal implementation or complete discontinuation, is recognised increasingly as contributing to apparent resistance to antihypertensive treatment. Using liquid chromatography tandem mass spectrometry to quantify a wide panel of antihypertensive drugs in plasma, Avataneo et al found that 18% of seemingly treatment‐resistant patients had undetectable concentrations of all their prescribed drugs. A similar proportion was reported by de Jager et al who found 16% of patients to be completely non‐adherent, with a further 52% of patients implementing suboptimally.…”
mentioning
confidence: 99%
“…Increased HR is an independent risk factor for cardiovascular events and mortality in the general population and various cardiovascular pathologies. High HR was recently shown to be associated with a poor adherence to medication regimens in patients with resistant hypertension . There are only a few prospective studies regarding the effect of HR reduction in heart failure and coronary artery disease.…”
mentioning
confidence: 99%